SALT BUSINESS GROWTH IN INDONESIA CASE: 4 DISTRICTS IN INDONESIA - Eny Widarni; Budi Sasongko; Suryaning Bawono; Murniati Murniati (Journal of Indonesian Applied Economics, 2020)
This paper aims to measure and forecast salt price based on cost and price rationality. The research employed quantitative method with Ordinary Least Square Model for measuring the rationality of salt and ordinary least square for forecasting salt cost and price in order to describe salt cost and price behaviour. Although the demand for salt increases every year, the abundant and cheap raw materials as well as the growth of the domestic production of salt business do not correlate positively with the growth of demand. We focus on measuring and forecasting price rationality as a proxy for the salt business prospects in Indonesia. We found that salt price formed at the time of the study was higher than the normal one. This is contrary to the motive theory of entrepreneurs, making the salt business in Indonesia remain a mystery.